analisis Pengaruh Gaya Kepemimpinan, Komitmen Organisasional Dan Budaya Organisasi Terhadap Kepuasan Kerja Dan Kinerja Pegawai - Sagrim, Sarteis Y (Universitas Sam Ratulangi, 1996)
The ability of a leader in mobilizing and empowering employees will effect employee performance. Certainly in the organization many factors that influence so that the goal can be achieved. While running of the organization or company certainly characterized by the behavior of individuals who are have an interest in their group. The results showed that the Leadership Style (X1) to Job Satisfaction Variable (Y1) is significant. Organizational Commitment (X2) on Job Satisfaction Variable (Y1) is significant. Leadership Style (X1) to variable Employee Performance (Y2) is significant. Organizational Commitment (X2) of the variable employee performance (Y2) is significant. Job Satisfaction (Y1) of the variable employee performance (Y2) is significant. Keywords: Leadership Style, Organizational Commitment and Cultural Organization on Job Satisfaction and Performance Officer